Samantha Shepardson: capstone - Shepardson, Samantha J., artist (Colorado State University. Libraries, 2018)
The artist's statement: As an artist I express myself best through the work I create. I am constantly inspired to create pieces that reflect my interests in music, nature, and pop culture. I find that through digital painting I can best combine my love for digital art and traditional art. With digital art I have endless possibilities to create pieces that otherwise I may not have been able to traditionally. Art is a vessel that carries my passions, and is closely in tune with my emotions. Through my work, I can express myself in a way that I can only show through art and creativity. Being an artist is an integral part of my identity. I am constantly striving for ways to improve my work and I am always hungry to learn new techniques and ways to create. Because identifying as an artist is so important to me, I will continue to learn more about how to improve myself and my skills.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.